Philippines : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report highlights institutional weaknesses that need to be addressed and proposes eight priority reform measures to strengthen the public investment management framework in the Philippines. This report reviews public investment management practices in the Philippines, using the IMF's Public Investment Management Assessment (PIMA) methodology. The PIMA findings could guide the upcoming Public Expenditure Review that is likely to be completed with the support of the World Bank. The PIMA provides a broad overview of institutional strengths and weaknesses along the public investment cycle. Strengthening public investment management in the Philippines would help maximize the return from the infrastructure investment in the coming years. While the public investment management institutions in the Philippines are generally comparable to emerging market economies, there is scope to improve performance. Standard methodologies for maintenance planning and costing of infrastructure assets exist for certain types of assets, and the same practice should be extended to other sectors. It would also be beneficial to establish a central monitoring mechanism to ensure the routine maintenance of major infrastructure assets.